Percepção da qualidade dos serviços prestados aos estudantes e egressos de pós-graduação da Universidade Federal de Santa Maria - Candé, Jailson Suleimane Gomes (2023)
Institutional self-assessment is a process permeated with self-knowledge, which enables the organization to meet its reality. It has the strategic role of uncovering challenges that plague the institution, as well as identifying windows of opportunity. In the academic sphere, selfevaluation is of commendable importance, as it has the potential to identify the quality or otherwise of the service provided, as well as to improve and enhance the performance of educational institutions in various areas. The aim of this research, using this management tool, is to analyze the perception of postgraduate students and graduates at the Federal University of Santa Maria (UFSM) regarding the functioning of their respective courses, and based on this, to provide proposals for improving the self-evaluation of Postgraduate Programs (PPGs) in Brazil. Initially, it is concerned with understanding aspects related to the origin and legal basis of institutional self-evaluation at undergraduate level, highlighting the National System for the Evaluation of Higher Education (SINAES), and at postgraduate level (PG), highlighting the Coordination for the Improvement of Higher Education Personnel (CAPES), and consequently the main concepts relating to the process of establishing undergraduate and PG courses in the country, as well as emphasizing the role played by the Brazilian state in this process. We therefore tried to make this work feasible by using a survey as a quantitative data collection procedure. In terms of data analysis, preference was given to descriptive statistical techniques and multivariate statistical analysis. The first involves the use of measures of central tendency, namely mean and median. The second involves factor analysis, t-test, ANOVA and multiple linear regression. The results show that there is a predominance of female PG students at UFSM, as well as graduates. There was a very low presence of black and indigenous people in the PG in the two segments investigated. The exploratory factor analysis reveals eleven factors that determine the quality of master's and doctoral courses. Of these factors, eight show significant differences between students at the two levels, and six factors show statistically significant differences between the segments. In the regression, five factors influence overall satisfaction with the course. Six variables also have a greater impact on the satisfaction of students/graduates in their relationship with their supervisor. It concludes that students and graduates have the capacity to carry out self-assessment of their courses/programs and, in the specific case of UFSM, those investigated have a good self-assessment of their institutions, demonstrating that their training is of high quality. And self-evaluation processes can be improved when the dimensions of evaluations are broadened, especially when it is recognized that users have the intelligence and wisdom necessary to contribute effectively.